Aktivitas Antioksidan Akar Bawang Merah Lokal Palu (Allium cepa Var Aggergatum L.) dengan Berbagai Kepolaran Pelarut: Antioxidant Activity of Local Shallot Roots (Allium cepa Var Aggregatum L.) in Palu City with Various Solvent - Nur Faidah; Nurhaeni; Ahmad Ridhay; Jusman; Abd. Rahman Razak; Syaiful Bahri (KOVALEN: Jurnal Riset Kimia, 2020)
Research on the antioxidant activity of the local onion roots of Palu (Allium cepa Var Aggregatum L.) with various polarity solvents has been carried out. This study aims to determine the potential of Palu local shallot root extract as an antioxidant and determine the IC50 value of the Palu local shallot root antioxidant activity. The method applied in this research is maceration using n-hexane, ethyl acetate, and ethanol. The extracts from each solvent were tested for their antioxidant activity by the DPPH method. The results of the study showed that the IC50 value in n-hexane extract, ethyl acetate extract, and ethanol extract were 579.98 ppm, 518.28 ppm 315.83 ppm and as a comparison used ascorbic acid obtained IC50 of 53.69 ppm. Based on the results obtained, the best antioxidant activity is in polar solvents (ethanol extract) compared to other solvents. Keywords: Antioxidants, roots, Palu local shallots, Allium cepa Var Aggregatum L.